Phytochemical Screening, Antibacterial Activity And Acute Oral Toxicity Of Aqueous And Ethanolic Extracts Of Harrisonia Abyssinica (Rutaceae) Leaf: Wild Plant Used In Benin Pharmacopeia - Ogougbé Raïmantou Egbèyèmi; Atindéhou Ménonvè Cynthia; Osséni Razack; Hounguè Rodrigue; Lalèyè Anatole; Djégo Julien (European Scientific Journal, ESJ, 2022)
Harrisonia abyssinica is a wild plant with multiple therapeutic properties used in traditional medicine in Benin. This study aimed at evaluating the preliminary phytochemical screening of large groups of secondary metabolites, antibacterial activity and acute oral toxicity of aqueous and ethanolic extracts of H. abyssinica leaves. Antibacterial activity evaluation was doing by microdilution method on bacterial (Staphylococcus aureus ATCC 25923, Escherichia coli ATCC 25922, Pseudomonas aeruginosa ATCC 27853, Enterococcus faecalis, Klebsiella pneumonia, Salmonella sp, Shigella sp and Vibrio cholerae). Minimum Inhibitory Concentration (MIC) was determined using Iodonitrotetrazolium salt as revelator. Wistar  rats were used for acute oral toxicity test in which single dose of 2000 mg/kg body weight of ethanolic and aqueous extract were administered; the control group received distilled water. Phytochemical screening revealed the presence of gallic tannins, alkaloids, reducing sugar, coumarins, quinones, steroids, terpene and saponosides. No toxicity was observed in rats. The LD50 obtained was greater than 2000 mg / kg bw of rats. No macroscopic and histological abnormalities were seen in kidneys and liver analyzes. Ethanolic extract of H. abyssinica showed a better activity than aqueous extract with a MIC of 1.25 mg / mL compared to 5 mg / mL for aqueous extract.